Unpackaging Demand for Water Service Quality : Evidence from Conjoint Surveys in Sri Lanka - Yang, Jui-Chen; Pattanayak, Subhrendu K.; Jonson, F. Reed; Mansfield, Carol; van den Berg, Caroline; Jones, Kelly (World Bank, Washington, DC, 2012)
In the early 2000s, the Government of Sri Lanka considered engaging private sector operators to manage water and sewerage services in two separate service areas: one in the town of Negombo (north of Colombo), and one stretching along the coastal strip (south from Colombo) from the towns of Kalutara to Galle. Since then, the government has abandoned the idea of setting up a public-private partnership in these two areas. This paper is part of a series of investigations to determine how these pilot private sector transactions (forming part of the overall water sector reform strategy) could be designed in such a manner that they would benefit the poor. The authors describe the results of a conjoint survey evaluating the factors that drive customer demand for alternative water supply and sanitation services in Sri Lanka. They show how conjoint surveys can be used to unpackage household demand for attributes of urban services and improve the design of infrastructure policies. They present conjoint surveys as a tool for field experiments and a source of valuable empirical data. In the study of three coastal towns in southwestern Sri Lanka the conjoint survey allows the authors to compare household preferences for four water supply attributes-price, quantity, safety, and reliability. They examine subpopulations of different income levels to determine if demand is heterogeneous. The case study suggests that households care about service quality (not just price). In general, the authors find that households have diverse preferences in terms of quantity, safety, and service options, but not with regard to hours of supply. In particular, they find that the poor have lower ability to trade off income for services, a finding that has significant equity implications in terms of allocating scarce public services and achieving universal water access.